Estudo do perfil farmacológico de novos complexos metálicos de hidrazonas derivadas de piridina e imidazóis - Angel Amado Recio Despaigne (2012)
In the present work, new pyridine and their copper(II), zinc(II), and tin(IV) complexes were obtained and characterized, imidazole-derived hydrazones were also estudied. Crystal structures of different compounds were determined. The pharmacological profile of allcompounds was investigated. Twelve imidazole-derived hydrazones were obtained. Four crystal structures were determinated. The antibacterial activity of the hydrazones was evaluated against Pseudomonasaeruginosa, Enterococcus faecalis and Staphylococcus aureus, but the compounds showed no appreciable activity. The antifungical activity of the compounds was evaluated against filamentous fungi Cladosporium cladosporioides and Aspergillus flavus and against Candidaalbicans and C. glabrata yeasts. 4(5)-imidazole-carboxaldehyde-benzoylhydrazone [4(5)ImPh],4(5)-imidazole-carboxaldehyde-para-nitro-benzoylhydrazone [4(5)ImpNO2Ph] and 4- (imidazole-1-yl)acetophenone-para-nitro-benzoylhydrazone [4ImAcpNO2Ph] showed lower MIC50 values than the reference drug nistatin, whereas compounds 4(5)ImpClPh and 4(5)ImpNO2Ph proved to be very active against C. cladosporioides. In this case, a possiblerelationship between the presence of electron withdrawing para-substituents and the increasing in antifungal activity was observed.Ten pyridine-derived hydrazones were obtained from 2-formylpyridine, 2acetylpyridine and 2benzoylpyridine. The crystal structures of six compounds were determined. These compounds exist as E and Z isomers in solution. The E isomer is the major form in 2-formylpyridine- and 2acetylpyridine-derived hydrazones, while the Z isomer predominates for 2-benzoylpyridine derivatives.The pharmacological profiles of these compounds were very interesting since they showed significant antifungal activity with MIC values lower or in the same order of magnitude as the reference drugs fluconazole and nistatin. In addition, the studied hydrazones showed highcitotoxic activity against U87 (expressing wild-type p53 protein) and T98 (expressing mutant p53 protein) glioma cells. Five hydrazones showed IC50 values in nanomolar concentrations with good therapeutic indexes. SAR studies suggested that stereo-electronic properties are importantfor citotoxic activity. In general, the 2-acetylpyridine-derived hydrazones showed better phamacological profile than the 2-formylpyridine- and 2-benzoylpyridine-derived analogues. Copper(II) and zinc(II) complexes were obtained with the pyridine-derived hydrazones.The zinc(II) complexes presented the general formula [Zn(HL)Cl2] whith a neutral hydrazone attached in a tridentate form to the metal ion in the E configuration. The crystal structures of six complexes were determined. Unfortunately, these complexes were inactive against fungi andbacteria. Copper(II) complexes were obtained with general formula [Cu(HL)Cl2] or [Cu(L)Cl]. In the first case, a neutral hydrazone is coordinated to the metal center as a tridentate chelatingligand, together with two chloride ions, while, in the second an anionic hydrazone is attached to the metal center along with one chloride ion. In all cases the hydrazone adopts the E configuration.The copper(II) complexes demonstrated an important pharmacological profile. Upon coordination, significant increase of the antimicrobial activity was observed. In fact, complexes [Cu(2AcpClPh)Cl] and [Cu(2BzpClPh)Cl], with 2-acetylpyridine-para-chlorophenylhydrazoneand 2-benzoylpyridine para-chlorophenylhydrazone, respectively showed lower values of MIC than fluconazole against C. albicans fungi. Some of these complexes also showed high cytotoxicity against U87 glioma cells, with a higher cytotoxic effect than the free hydrazones. Studies of the interaction of the complexes with DNA revealed that some of the complexes showed a typical intercalation profile while others probably present a different way of interaction. Tin(IV) complexes with the general formula [RSn(HL)Cl2] R = n-butyl or R = phenyl were prepared with the pyridine-derived hydrazones. In all complexes an anionic hydrazone iscoordinated to metal center as a tridentate ligand together with a phenyl or a n-butyl group and two chloride ions. The crystal structures of seven organotin complexes were determined. The complexes showed higher antifungal activity than their respective ligands against A. flavus, C.glabrata e C. albicans. The tin(IV) complexes were fluorescent with quantum yield values similar to quinine sulfate. An increase in the intensity of fluorescence was observed with the addition of smallamounts of micelar surfactant tween. This property could make these complexes useful as fluorescent probes.